ANALISIS KUANTITATIF AKTIVITAS TEKTONIK R ELATIF DI PEGUNUNGAN BATURAGUNG JAWA TENGAH - Rahmi Mulyasari; Budi Brahmantyo; Supartoyo Supartoyo (Fakultas Ilmu dan Teknologi Kebumian (FITB), Institut Teknologi Bandung (ITB), 2017)
Neotectonics is a major controlling landform development in tectonically active regions, and it has significantly affected fluvial systems and mountain – front landscapes in the Baturagung Mountain, Central Java. This area is one of areas in Indonesia which is prone to earthquake from subduction zone in Indian Ocean and active fault in land. The earthquake sources from active fault probable from Opak and Dengkeng fault located in Baturagung Mountain. To assess tectonic activities in the area used quantitative approach (morphometric analysis). Morphometric analysis was used to identify the relative tectonic activity index (RTAI) in Baturagung Mountain consist of 5 parameters geomorphic indices: basin asymmetry (AF), hypsometric integral and curve (Hi and Hc), stream length gradient index (SL), basin indices (Bs), and mountain – front sinuosity (Smf). RTAI in this area is divided into three classes: Class 2 (high), Class 3 (moderate), and Class 4 (low). Distribution of RTAI in 65 subbasins area (207.2 km2) is: about 0.6% of watershed area (1.32 km2) Class 2; 58.9% (122.1 km2) of Class 3; and 40.4% (83.75 km2) Class 4. All of morphometry analysis generally indicates this area more influenced by tectonics than erosion. The results are consistent with field observations on landforms and geology.